2004
DOI: 10.1097/00008571-200403000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CYP3A5 and MDR1 (ABCB1) polymorphisms on cyclosporine and tacrolimus dose requirements and trough blood levels in stable renal transplant patients

Abstract: Cyclosporine and tacrolimus are immunosuppressive drugs largely used in renal transplantation. They are characterized by a wide inter-individual variability in their pharmacokinetics with a potential impact on their therapeutic efficacy or induced toxicity. CYP3A5 and P-glycoprotein appear as important determinants of the metabolism of these drugs. The objective of this study was to investigate the effect of CYP3A5 and MDR1 (ABCB1) polymorphisms on cyclosporine and tacrolimus dose requirements and trough blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
299
4
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(325 citation statements)
references
References 26 publications
18
299
4
4
Order By: Relevance
“…Dennis et al [18] reported that MDR1 C3435T did not influence the dose-adjusted trough blood concentration of CsA in stable renal transplant patients. Consistent results were obtained in another study involving American renal transplant patients [19] . Crettol et al [20] also reported that MDR1 genotypes did not influence the dose-adjusted trough blood concentration of CsA in transplant recipients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Dennis et al [18] reported that MDR1 C3435T did not influence the dose-adjusted trough blood concentration of CsA in stable renal transplant patients. Consistent results were obtained in another study involving American renal transplant patients [19] . Crettol et al [20] also reported that MDR1 genotypes did not influence the dose-adjusted trough blood concentration of CsA in transplant recipients.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, high inter-individual heterogeneity in the MDR1 gene, influencing the metabolism of digoxin [15][16][17] , cyclosporin [18][19][20] , tacrolimus [21][22][23] and amlodipine [24] , has been described. In the present study, we explored the association of MDR1 SNPs with CsA dose requirements and adjusted concentration in renal recipients co-treated or not with diltiazem.…”
Section: Discussionmentioning
confidence: 99%
“…There were four studies that did not show the concentrations of *1/*1 and *1/*3 genotypes separately. 16,23,26 In addition, in the study of Haufroid et al, 21 there was no subject with *1/*1 genotype. Among all the subjects, the frequencies of CYP3A5*1/*1 þ *1/*3 (expresser) and *3/*3 (non-expresser) were 34.73 and 65.27%, respectively.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Five studies were from western countries, including France, the Netherlands, Belgium, United States and Germany, 14,16,[20][21][22] whereas 9 were from Asian countries, of which 6 were from China, [11][12][13][23][24][25] and the remaining 3 were performed in India, Singapore and Malaysia, respectively. [26][27][28] Most of the CsA administrations were multiple oral doses adjusted according to C 0 or C 2 levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As these genes have functional polymorphisms affecting drug metabolism, there have been many pharmacogenetics studies. [4][5][6][7][8][9] Because this type of study helps us predict the patient's biological response to a drug, we can avoid the side effects and provide suitable therapy for each individual.…”
Section: Introductionmentioning
confidence: 99%